BIMBINGAN ANAK YANG KESULITAN MEMBACA PADA ANAK SD - Fatma Dewani Harahap (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2026)
Reading skills are an important foundation in learning in elementary schools. However, there are still many students at the elementary school level who have difficulty reading, at SDN 100810 in Hiteurat, North Padang Lawas district, there are students who still have difficulty reading. This community service program aims to increase the reading interest and literacy skills of 3rd and 4th grade students at the school through a participatory approach, with activities such as learning houses, group reading, creative writing, and literacy games. Based on initial observations, 80 percent of students had difficulty writing and were able to construct sentences well. Evaluation results after providing guidance to students showed that this program was successful in increasing students' interest and reading skills, with 85 percent of students showing increased reading comprehension. Factors such as interest, interactive learning methods, and teacher and parental support played a significant role in the success of this program. This program is expected to become a model for literacy development in other schools. ABSTRAKKemampuan membaca merupakan fondasi penting dalam pembelajaran di sekolah dasar. Namun, masih terdapat banyak siswa di tingkat Sekolah Dasar (SD) yang mengalami kesulitan dalam membaca, di SDN 100810 di Hiteurat kabupaten Padang Lawas Utara terdapat siswa yang masih kesulitan membaca. Program pengabdian masyarakat ini bertujuan untuk meningkatkan minat baca dan kemampuan literasi siswa kelas 3 dan 4 di sekolah tersebut melalui pendekatan partisipatif, dengan kegiatan seperti rumah belajar, bacaan berkelompok, menulis kreatif, dan permainan literasi. Berdasarkan observasi awal terdapat 80 persen siswa mengalami kesulitan menulis dan  mampu  menyusun  kalimat  dengan baik. Hasil evaluasi setelah dilakukan bimbingan kepada siswa menunjukkan bahwa program ini berhasil meningkatkan minat dan kemampuan membaca siswa, terdapat 85 persen siswa menunjukkan peningkatan pemahaman bacaan.  Faktor-faktor  seperti  minat,  metode  pembelajaran interaktif, serta dukungan guru dan orang tua berperan signifikan dalam keberhasilan program ini. Program ini diharapkan dapat menjadi model dalam pengembangan literasi di sekolah-sekolah lain.